The Mediating Role of Career Calling in the Relationship Between Family-Supportive Supervisor Behaviors and Turnover Intention Among Public Hospital Nurses in China - Leigang Zhang; Tingting Jin; Huaibin Jiang (Elsevier, 2020)
Purpose: This study explored the mediating effect of career calling in the relationship between family-supportive supervisor behaviors and turnover intention among nurses. Methods: Data were gathered from 563 nurses enrolled in eight public hospitals in China. They were required to complete measures of family-supportive supervisor behaviors, career calling, and turnover intention. Hierarchical multiple regression analysis and the bootstrapping procedure were used to examine the mediating role of career calling. Results: Family-supportive supervisor behaviors were positively associated with career calling, but negatively associated with turnover intention. Furthermore, career calling partially mediated the relationship between family-supportive supervisor behaviors and turnover intention. Conclusion: This study provides strong evidence for an increasing body of work that emphasizes the importance of nursing leaders engaging in family-supportive behaviors for increasing employee career calling and reducing turnover intention.